Réponses

Meilleure réponse !
2014-04-19T00:13:05+02:00
Bonsoir,

1) f(x)=\dfrac{(-2x+4)(x-1)}{(6+2x)(5-x)}

racines : 
Numérateur : -2x+4 = 0 ==> -2x = -4
                                  ==> x = 2
                    x-1 = 0 ==> x = 1
Dénominateur : 6+2x = 0 ==> 2x = -6
                                     ==> x = -3
                       5-x = 0 ==> -x = -5
                                  ==> x = 5

\begin{array}{|c|ccccccccccc||}x&-\infty&&-3&&1&&2&&5&&+\infty\\ -2x+4&&+&+&+&+&+&0&-&-&-&\\ x-1&&-&-&-&0&+&+&+&+&+&\\  6+2x&&-&0&+&+&+&+&+&+&+&\\5-x&&+&+&+&+&+&+&+&0&-&\\Quotient&&+&|&-&0&+&0&-&|&+&\\\\\end{array}


2) \dfrac{(-2x+4)(x-1)}{(6+2x)(5-x)}>0\Longleftrightarrow x\in]-\infty;-3[\ \cup\ ]1;2[\ \cup\ ]5;+\infty[

Par conséquent,  S=]-\infty;-3[\ \cup\ ]1;2[\ \cup\ ]5;+\infty[
merci bcp cest vraiment gentil !!!!!!! :D